PENGARUH PEMBERIAN VITAMIN B KOMPLEK TERHADAP GEJALA PREMENSTRUAL SYNDROME (PMS) - Lelly Aprilia Vidayati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Premenstrual syndrome is stillexperienced by student, namely 32 students.According to Anityo researche (2014), theanalysis of the effect of vitamin B complexonphysical symptoms and premature psychology ofthe syndrome result in significant result, this isshown from reduced to loss of physical andpsychology complaint. From the results ofpreliminary study on the first level students ofD3 midwifery STIKES NHM there are 32 (84%)of students who experienced premenstrualsyndrome. The aim of the research is theinfluence of vitamin B complex towardsymptoms of premenstrual syndrome. The research design used preexperimental design with one group pretestposttest approach. The independent variable isvitamin B complex, while the dependent variableis students who experience premenstrualsyndrome. The population is 32 respondents andthe sample is 30 respondents. The samplingtechnique used in this study is random sampling.Data collection used questionnaires andinterviews, then analyzed using Paired t test. The average symptom of premenstrualsyndrome before being given vitamin B complexis 38.43 and after being given is 22.37. Theresult of data analysis with Paired t test showedthe value of P Value (0.000) with significancelevel α (0.05), it means value of P Value < α,meaning there is influence of vitamin B complextoward symptoms of premenstrual syndrome. thesynthesis vitamin B complex helps ofneurotransmitter in the brain so that it producesserotonin which plays a role in regulatingmental process, mood, while serotonin activityis related to premenstrual syndrome.